Efficient near-infrared light-emitting diodes based on liquid PbSe quantum dots. (2nd May 2017) - Wang, Yu; Bai, Xue; Wang, Tongyu; Yan, Long; Zhang, Tieqiang; Zhang, Yu; Yu, William W
Abstract: Recently, near-infrared light-emitting diodes (NIR LEDs) based on PbSe quantum dots (QDs) have attracted considerable attention due to their facilely tunable emission wavelength, as well as high quantum yield. However, the low external quantum efficiency (EQE) of these LEDs has restricted their actual applications because of the non-radiative recombination caused by the aggregation in the solid-state QD films. Therefore, we proposed in this work to employ the liquid-type structure in NIR LEDs base on PbSe QDs, which exhibited the main advantages relying on the fact that the liquid structure could prevent the active layer from self-aggregation and improve the device stability. The emission intensity of these NIR LEDs was optimized by tuning the concentration of PbSe QDs. Besides, the radiation power of PbSe QD-based devices with different emission wavelengths was analyzed under different biases, and the maximum EQE of NIR LEDs was confirmed to be 5.3%. This result represents the highest record among the reported NIR QD-LEDs, indicating this kind of liquid-type NIR LEDs is promising for commercial applications.